Low-Stakes Opportunism. (April 2013) - Jap, Sandy D.; Robertson, Diana C.; Rindfleisch, Aric; Hamilton, Ryan
In this research, the authors develop a theory addressing why people act opportunistically when the stakes (i.e., payoffs) are low. Transaction cost theory suggests that opportunistic behavior is more likely under high-stakes conditions. The authors identify rapport as an important moderator of this relationship. Through a series of three studies, they find that high-stakes opportunism appears to occur only when rapport is low. In contrast, when rapport is high, this relationship reverses, such that opportunism is actually more likely when the stakes are low than when they are high. The authors attribute these findings to differences in reasoning and find that when rapport is high and the stakes are low, people are better able to justify their actions by employing morally malleable reasoning. Thus, this research offers insights into an important form of opportunism that has been largely absent from transaction cost theory.